(untitled) (Research, Society and Development, 2020)
Objective: to identify in the literature the difficulties encountered in adhering to the safe surgery checklist in hospitals to increase patient safety in health organizations with surgical centers. Method: This is an integrative review of the literature that sought to verify the difficulties encountered in adherence to the safe surgery checklist in hospitals. Results: It was found that there is unanimity regarding the importance of using checklists in surgeries, with one of the literature pointing out the occurrence of an adverse event in a unit where there was no implementation. It was identified the lack of training aimed at the insertion of the checklist in institutional educational actions, being the main difficulty pointed out the lack of human resources to conduct the checklist in several operating rooms and the multiple surgeries performed simultaneously. It was also possible to understand that the use of the checklist can generate discomfort in the professional who conducts it. No relationships were identified between adverse events in surgical patients and the implementation of checklists. Conclusion: the use of the checklist is neglected in its completion and there are numerous difficulties for its implementation, besides the lack of motivation for its effective insertion by surgical teams. The absence of a culture of registration/notification according to the analyzed literature was evidenced, a condition that can interfere in the management of indicators aimed at the implementation of the goal "safe surgery" and best practices in these units.